Three Terminal Perovskite/Silicon Solar Cell with Bipolar Transistor Architecture - Gemma Giliberti; Francesco Di Giacomo; Federica Cappelluti (Energies, 2022)
Solar photovoltaic energy is the most prominent candidate to speed up the transition from the existing non-renewable energy system to a more efficient and environmentally friendly one. Currently, silicon cells dominate the photovoltaic market owing to their cost-effectiveness and high efficiency, nowadays approaching the theoretical limit. Higher efficiency can be achieved by tandem devices, where a wide bandgap semiconductor is stacked on top of the silicon cell. Thin-film perovskite technology has emerged as one of the most promising for the development of silicon-based tandems because of the optimal perovskite opto-electronic properties and the fast progress achieved in the last decade. While most of the reported perovskite/silicon tandem devices exploit a two-terminal series connected structure, three-terminal solutions have recently drawn significant attention due to their potential for higher energy yield. In this work, we report for the first time a theoretical study, based on validated optical and electrical simulations, of three-terminal perovskite/silicon solar cells employing a hetero-junction bipolar transistor structure. With respect to other three-terminal tandems proposed so far, the transistor structure can be implemented with rear-contact silicon cells, which are simpler and more common than interdigitated back-contact ones.